Examining and adapting the information–motivation–behavioural skills model of medication adherence among community-dwelling older patients with multimorbidity: protocol for a cross-sectional study - Yang, Chen; Hui, Zhaozhao; Zeng, Dejian; Liu, Li; Lee, Diana Tze Fan (BMJ open, 2020)
IntroductionMultimorbidity is highly prevalent among older patients and has been shown to be associated with poor health outcomes and lower quality of life. Adherence to medication treatments is essential in order to maximise the efficacy of treatments and improve health outcomes. However, nearly half of the older patients with multimorbidity fail to adhere to their medications, which can result in an increased risk of adverse health events, lower quality of life and higher healthcare cost. Only a few studies have explored the underlying mechanism and influencing factors of medication adherence among older patients with multimorbidity, which are inadequate to provide robust evidence for the development and evaluation of the medication adherence interventions. This study aims to examine and adapt the information–motivation–behavioural skills (IMB) model, a widely used social behaviour theory, to explain the medication adherence behaviour among community-dwelling older patients with multimorbidity.Methods and analysisA cross-sectional study will be conducted in community settings in China. Around 309 older patients with multimorbidity will be recruited to complete questionnaires on adherence knowledge, adherence motivation, adherence self-efficacy, medication adherence, medication treatment satisfaction, depressive symptoms, treatment burden, disease burden and basic demographic information. Structural equation modelling will be used to analyse and validate the relationships among variables in the IMB model.Ethics and disseminationThis study has been approved by the Survey and Behavioral Research Ethics Committee of the Chinese University of Hong Kong (reference number SBRE-18-675). The study results will be published in peer-reviewed journals and presented in academic conferences and workshops.Trial registration numberChiCTR1900024804.